Talak dalam hukum islam: analisis fiqh munakahat dan implikasi sosialnya - Masykur, Danial arba asyakir (Maliki Interdisciplinary Journal, 2025)
Divorce is an important aspect of Islamic family law that has a significant impact on family life. This article discusses the definition of divorce, its legal basis, pillars and requirements, as well as the various types of divorce from the perspective of fiqh munakahat. In addition, this study highlights the factors that cause divorce and its socio-psychological implications, especially for women and children. This research uses a literature study method with reference to the Qur’an, hadith, fiqh books, and Indonesian laws and regulations. The results of the study show that divorce is not only a private matter, but also has a broad social impact. A comprehensive understanding of divorce law is necessary to maintain the welfare of families and society.